Management of an hypopharyngeal fistula following open diverticulectomy for giant Zenker's diverticulum: a case report - Bourouail, Othmane; Hamada, Abdelilah; Kada, Ali; Halim, El Mustapha; Njoumi, Noureddine; Yaka, Mbarek; Elfahssi, Mohammed; Elhjouji, Abdelrrahman; Aitali, Abdelmounaim (Frontiers in Surgery, 2026)
Postoperative hypopharyngeal fistula is an uncommon yet serious complication of open surgery for Zenker's diverticulum, with an incidence of approximately 1%–4%. It is associated with local infection, malnutrition, deterioration of the patient's general condition, and an increased risk of subsequent esophageal stricture. The most valuable therapeutic approach is based on surgical reintervention with reinforced closure, adequate drainage, antibiotic therapy, and optimization of hemodynamic and nutritional parameters. Other methods may also be used, including digestive diversion or conservative management strategies such as radiologically guided drainage. We report the case of a 54-year-old man with a large symptomatic Zenker diverticulum who underwent open mechanical diverticulectomy. The immediate postoperative course was uneventful, and the patient was discharged on day six; however, four days later he was readmitted with painful cervical swelling and signs of infection. Cervical CT with oral contrast demonstrated an extensive hypopharyngeal fistula. Broad-spectrum antibiotic therapy was initiated, and on the second day of hospitalization the patient underwent surgical re-exploration with primary closure of the defect reinforced by a muscular flap and adequate drainage, followed by enteral nutritional support. The postoperative evolution was favorable, with complete closure of the fistula. During follow-up, an esophageal stenosis developed but was successfully managed by endoscopic dilatation. This case highlights the rarity and the management challenges of hypopharyngeal fistula following Zenker's diverticulectomy. It underscores the importance of early recognition and timely surgical intervention using a reinforced closure technique, which is considered the most reliable approach according to current literature for managing fistulas in the hypopharyngeal region. Coordinated postoperative care with rigorous monitoring remains essential to achieve favorable outcomes, despite the potential for long-term sequelae such as esophageal stricture.